Tamoxifen attenuates dialysate-induced peritoneal fibrosis by inhibiting GSK-3β/β-catenin axis activation. Issue 6 (21st November 2018) - Yan, Pengpeng; Tang, Huanna; Chen, Xiaoying; Ji, Shuiyu; Jin, Wei; Zhang, Jiaming; Shen, Jia; Deng, Hao; Zhao, Xiang; Shen, Quanquan; Huang, Hongfeng
Abstract : Peritoneal fibrosis is a severe complication arising from long-term peritoneal dialysis (PD). Tamoxifen (Tamo) has been clinically proven effective in a series of fibrotic diseases, such as PD-associated encapsulating peritoneal sclerosis (EPS), but the mechanisms underlying Tamoxifen's protective effects are yet to be defined. In the present study, C57BL/6 mice received intraperitoneal injections of either saline, 4.25% high glucose (HG) PD fluid (PDF) or PDF plus Tamoxifen each day for 30 days. Tamoxifen attenuated thickening of the peritoneum, and reversed PDF-induced peritoneal expression of E-cadherin, Vimentin, matrix metalloproteinase 9 (MMP9), Snail, and β-catenin. Mouse peritoneal mesothelial cells (mPMCs) were cultured in 4.25% glucose or 4.25% glucose plus Tamoxifen for 48 h. Tamoxifen inhibited epithelial-to-mesenchymal transition (EMT) as well as phosphorylation of glycogen synthase kinase-3β (GSK-3β), nuclear β-catenin, and Snail induced by exposure to HG. TWS119 reversed the effects of Tamoxifen on β-catenin and Snail expression. In conclusion, Tamoxifen significantly attenuated EMT during peritoneal epithelial fibrosis, in part by inhibiting GSK-3β/β-catenin activation.